Commissive Illocutionary Act Used in Turning Red Movie - Gede Mahar Ditriwan; I Nyoman Tri Ediwan; I Made Netra (CV. Ulil Albab Corp, 2023)
This article is entitled Commissive Illocutionary Act Used in Turning Red Movie. The aims of this article are to identify the types of commissive illocutionary act used by the characters and explain the context of situation that support the character utterances that belongs to commissive illocutionary act in Turning Red movie. The movie titled Turning Red as the data source. The descriptive qualitative method was applied to analyze the data in this study. This article used Searle & Vanderveken (1985) theory of commissive illocutionary act and Holmes (2013) theory of the context of the situation. The results of this study show that five types of commissive illocutionary acts proposed by Searle and Vanderveken (1985) were found in all data sources. They were promise, threat, accept, refuse, and offer. The most frequent type of commissive illocutionary act found is Promise. The act of promise in this movie was used to inform if the action in the speech act promises to be performed at a future time. Then, context of the situation is used to support the understanding of how the utterance occurred and the purpose behind the utterance.